Urgensi Kajian Sejarah dalam Pendidikan Islam dan Relevansinya di Abad 21 - Khoirunnisa Khoirunnisa; Abdul Fikri (KOLONI, 2023)
In the 21st century, all walks of life are affected by technology. In this century, the movement of information is very fast and widely spread without regard to geographical boundaries. This is what drives the development of science and technology in this century. Education, especially Islamic education, seems to be increasingly open to the progress of the times. Unfortunately, the debate about the relevance of historical studies in the context of the development of science and technology, which is the vision of education today, is increasingly prominent. This is based on the view that historical studies are only limited to discussing the past, which is certainly very contrary to the current understanding and vision of education which is identical to the problems of the present and the future. This research, using a qualitative library research approach, shows that historical studies are still very relevant to the current educational paradigm, especially as an educational and inspirational tool for current and future generations. Therefore, the development of historical studies needs to be implemented in an effort to comprehensive and actualise historical values in the present context.